THE EFFECTS OF R&D EXPENDITURES ON ECONOMIC GROWTH IN OECD COUNTRIES - Amanah Abdulkadir; Wendra Afriana; Harry Azis (Airlangga Journal of Innovation Management, 2020)
This study investigates the relationship between R&D and economic growth in 33 OECD countries. This research uses panel data method. The results showed that there are three independent variables that affect economic growth. Namely, gross domestic expenditure on R&D, government research, and internet access. However, gross domestic expenditure on R&D and government research has a negative impact on economic growth. With the t-statistics of -2.944775 and -0.203002, respectively. While the t-statistic for internet access variable is 2.460783. This shows that only the internet access variable has a positive effect on economic growth. Meanwhile, the variable access to computers from home does not affect economic growth, because the probability is 0.0674 or> 0.05. These findings do not support the general hypothesis that R&D expenditures will have a positive impact on economic growth. The research agenda must be clear, substantive and short-term and must be implemented as a consideration in making decisions. So that every investment in R&D spending provides benefits with the hope of creating new innovations, so that the Indonesian economy grows positively.